2020
DOI: 10.1002/jlb.2mr0220-549r
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1: A master regulator of cellular responses in inflammation, injury resolution, and tumorigenesis

Abstract: ICAM‐1 is a cell surface glycoprotein and an adhesion receptor that is best known for regulating leukocyte recruitment from circulation to sites of inflammation. However, in addition to vascular endothelial cells, ICAM‐1 expression is also robustly induced on epithelial and immune cells in response to inflammatory stimulation. Importantly, ICAM‐1 serves as a biosensor to transduce outside‐in‐signaling via association of its cytoplasmic domain with the actin cytoskeleton following ligand engagement of the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
318
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 591 publications
(395 citation statements)
references
References 193 publications
14
318
0
8
Order By: Relevance
“…Both proteins were more abundant in stimulated MIO-M1 cells as well as in stimulated primary RMG (Table 1 and Figure 1), which is in line with previous findings of increased ICAM1 expression after stimulation with LPS or IFN-γ in murine and rat Müller cells [71,72]. ICAM1 mediates the adhesion and migration of leukocytes through the endothelial barrier into inflamed tissue (reviewed in [73][74][75]), and it has been shown to regulate the migration of Th1-and Th17-T-cells through simulated human retinal endothelium [76]. High expression levels of these adhesion molecules have been reported in posterior uveitis in humans [77] and in murine EAU with VCAM1 expression in the perivascular extensions of RMG in uveitic murine eyes [78].…”
Section: Discussionsupporting
confidence: 88%
“…Both proteins were more abundant in stimulated MIO-M1 cells as well as in stimulated primary RMG (Table 1 and Figure 1), which is in line with previous findings of increased ICAM1 expression after stimulation with LPS or IFN-γ in murine and rat Müller cells [71,72]. ICAM1 mediates the adhesion and migration of leukocytes through the endothelial barrier into inflamed tissue (reviewed in [73][74][75]), and it has been shown to regulate the migration of Th1-and Th17-T-cells through simulated human retinal endothelium [76]. High expression levels of these adhesion molecules have been reported in posterior uveitis in humans [77] and in murine EAU with VCAM1 expression in the perivascular extensions of RMG in uveitic murine eyes [78].…”
Section: Discussionsupporting
confidence: 88%
“…Constant human recombinant IFN-a treatment also resulted in enhanced survival, which was associated with an IFN-g-mediated decrease of parasitemia, expression of intracellular adhesion molecule-1 (ICAM-1 or CD54) in the brain, and CD8 + T cells sequestration (Vigario et al, 2007) (Figure 3B). ICAM-1 is a cell surface glycoprotein that is typically expressed on endothelial and immune cells; it plays an important role in cell-cell adhesion, extravasation, signal transduction, and inflammation (Bui et al, 2020). Increased expression of ICAM-I in the brain microvasculature has been implicated in the development of cerebral malaria (CM).…”
Section: Protective Ifn-i Responses Against Parasitemia and Host Mortmentioning
confidence: 99%
“…Meanwhile, in MS patients, Barry et al, found that EVs released from activated T cells can promote monocyte recruitment and upregulate intercellular cell adhesion molecule-1 (ICAM-1) in endothelial cells as well as macrophage-1 antigen (Mac-1) expression in monocytes. Activated monocyte expression of Mac-1 integrin and its binding to ICAM-1 is an essential step in the transendothelial migration of inflammatory cells ( 50 ). Brain endothelium-derived microvesicles have been shown to be involved in the activation of CD4 + and CD8 + T lymphocytes through the expression of MHCII and CD40 molecules ( 51 ), suggesting that EVs are involved in the pathogenesis of MS. Azimi et al, found that miR-326a to be overexpressed in T cell-derived exosomes from MS patients ( 52 ).…”
Section: Evs and Autoimmune Diseasesmentioning
confidence: 99%